2018
DOI: 10.5935/1984-0063.20180011
|View full text |Cite
|
Sign up to set email alerts
|

Acute response to 7-day therapy with CPAP in patients with moderate to severe obstructive sleep apnea and cardiac arrhytmia

Abstract: IntroductionObstructive Sleep Apnea (OSA) has been associated with an elevated risk of cardiac arrhythmia. Continuous positive airway pressure (CPAP) is the selected treatment for moderate to severe OSA and could improve arrhythmias in the long term. However, the acute effect of CPAP has not been studied in detail.MethodsWe conducted a prospective study with 25 patients with moderate to severe OSA diagnosed by home respiratory polygraphy (RP) and arrhythmia and/or pauses in 24-hour Holter ECG. We analyzed infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Altmay et al ( 27 ) observed patients with normal preoperative pulmonary function and CPAP use did not improve lung function after cardiac surgery. Furthermore, short-term CPAP treatment cannot reduce postoperative cardiac arrhythmias ( 28 , 29 ). There are many factors that induce postoperative arrhythmias, pacemaker use, reintubation, and pneumonia, such as poor cardiac function, hypoxia, and malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Altmay et al ( 27 ) observed patients with normal preoperative pulmonary function and CPAP use did not improve lung function after cardiac surgery. Furthermore, short-term CPAP treatment cannot reduce postoperative cardiac arrhythmias ( 28 , 29 ). There are many factors that induce postoperative arrhythmias, pacemaker use, reintubation, and pneumonia, such as poor cardiac function, hypoxia, and malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…In this population, most groups have evaluated the long-term benefits of the use of continuous positive airway pressure, although no studies have demonstrated a positive short-term impact. 4 By inference, at the timing considered, screening and detection may be useless if no effective therapy can be used.…”
Section: To the Editorsmentioning
confidence: 99%